Hypofractionated radiation therapy and wound healing after massive sarcoma resection: Case report and review of the literature. (June 2021) - Allen, Michael; Silvino, Daniella; Kamrava, Mitchell; Shon, Wonwoo; Brien, Earl
Abstract: Introduction: Large high-grade sarcomas are commonly managed with five weeks of pre-operative radiation with chemotherapy followed by surgical resection. Wound complications occur in about one out of three patients with this regimen. Hypofractionated radiation therapy (HFRT) is a developing pre-operative approach that delivers radiation over a shorter duration of 5–10 treatments. Presentation of case: Two patients underwent HFRT with neoadjuvant chemotherapy followed by tumor resection. The first patient had high-grade de-differentiated liposarcoma, and the second patient a high-grade myxofibrosarcoma. Neither patient developed post-operative wound complications despite the massive tumor size. Discussion: Less is understood regarding rates and risk factors associated with wound complications using this shortened radiation approach. With attention to surgical detail, and advancing radiation delivery technologies, rates of complications can be minimized. Conclusion: We discuss our experience with a neoadjuvant hypofractionated chemoradiation protocol in two patients with large volume sarcomas resected from the chest wall and the thigh who did not develop acute wound complications. Further evaluation of this shortened regimen is warranted. Highlights: Wound complications are common after sarcoma resection with preoperative radiation. Hypofractionated Radiation Therapy (HFRT) may be a safe alternative to conventional dose radiation. HFRT can be utilized with massive volume sarcomas safely.